UPAYA MENINGKATKAN MINAT BELAJAR DAN HASIL BELAJAR SISWA MELALUI PENERAPAN STRATEGI PEER LESSON DI KELAS V SD NEGERI 34 BANDA ACEH TAHUN PELAJARAN 2013/2014 - Maisarah Maisarah (JURNAL TEMATIK, 2015)
This study aims to determine whether the strategy of eye Lessons can improve learning and learning outcomes PAI in class V SDN 34 in Banda Aceh. This study uses a study of action (action research) in the fifth grade students of SDN 34 in Banda Aceh. So for Islamic Education student learning outcomes in class V SDN 34 in Banda Aceh in the second cycle is 90.82. Thus it can be said that learning to recognize indicators of the messenger of Allah, the value obtained is very satisfactory. Improve student learning outcomes after the second cycle is done due to improvements in learning strategies used subjects.